Long‐term degradation rate of crystalline silicon PV modules at commercial PV plants: An 82‐MWp assessment over 10 years. (3rd August 2021) - Pascual, Julio; Martinez‐Moreno, Francisco; García, Miguel; Marcos, Javier; Marroyo, Luis; Lorenzo, Eduardo
Abstract: Due to high competitiveness in the PV sector, despite the low degradation rate of crystalline silicon PV modules (below 0.5%/year), it is still important for utilities to know its actual value due to its impact on energy yield and hence, profitability, over the lifetime of a PV plant. However, uncertainties related to both the influence of downtime periods due to problems that may appear under normal operation of a commercial PV plant and to the measurement of degradation rates at PV plant level make this a challenging task. In order to obtain a significant value, in this paper, three measuring methods with different uncertainty sources are used for 82 MWp of PV modules on different locations in Spain and Portugal over 10 years. According to the different methods used and PV plants analyzed, excluding PV plants with problems, a range of degradation rates between 0.01 and 0.47%/year has been found. The overall average value observed is 0.27%/year. The findings of this work have also revealed the great importance of good operation and maintenance practices in order to keep overall low degradation rates. Abstract : Degradation rate of PV modules has been measured using different methods with independent uncertainty sources in 13 PV plants accounting for 82 MWp of PV modules at different locations in Spain and Portugal over 10 years. According to the different methods used and PV plants analyzed, excluding PV plants with problems, a range of degradation rates between 0.01%/year and 0.47%/year has been found. The overall average value observed is 0.27%/year.